Implementasi Sistem Pakar Diagnosis Penyakit Diabetes Mellitus Menggunakan Metode Fuzzy Logic Berbasis Web - Masykur, Fauzan (Universitas Diponegoro, 2012)
Number of patients with Diabetes Mellitus increases from year to year. This is due to late diagnosis of disease and also because of an unhealthy lifestyle. The disease usually does not realize that the disease Diabetes Mellitus. In this study, made ​​an enforcement system diseases Diabetes Mellitus with the Sugeno method. The variables supporting the diagnosis of the disease are used in the formation of a fuzzy set. Fuzzy set will be processed by the Sugeno method to produce a decision. Designed application has been tested with the involvement of medical records from physician diagnosis, the decision of the resulting application is the same as physician diagnosis listed in medical records. In general, web-based applications can be used as a tool in the diagnosis of Diabetes Mellitus. Keywords : Fuzzy logic; Expert system; Diabetes mellitus; Web-based